2003
DOI: 10.1063/1.1609235
|View full text |Cite
|
Sign up to set email alerts
|

Studying the local chemical environment of sulfur atoms at buried interfaces in CdS/ZnSe superlattices

Abstract: Soft x-ray emission spectroscopy has been employed to study the local chemical environment of sulfur atoms in sulfide II–VI semiconductors (ZnS, CdS, HgS) and CdS/ZnSe superlattices. By using fluorescence transitions involving metal d-state-derived valence bands and S 2p core holes, a distinction between S–Zn and S–Cd bonds in the superlattices can be made. We find that, in addition to the expected S–Cd bonds, interfacial S–Zn bonds are present in superlattices grown at 170 °C, and that the amount of S–Zn bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The ability of soft X-ray emission spectroscopy (XES) to assist in studies of electronic structure and chemical bonding of advanced materials was again demonstrated in the literature this year. Heske et al 337 studied the local chemical environment of S atoms in sulfide II-VI semiconductors (ZnS, CdS, HgS) and CdS/ZnSe superlattices. A distinction was reported between S-Zn and S-Cd bonds in the superlattices using fluorescence transitions involving metal d-state derived valence bands and S 2p core holes.…”
Section: Chemical State Analysis and Speciationmentioning
confidence: 99%
“…The ability of soft X-ray emission spectroscopy (XES) to assist in studies of electronic structure and chemical bonding of advanced materials was again demonstrated in the literature this year. Heske et al 337 studied the local chemical environment of S atoms in sulfide II-VI semiconductors (ZnS, CdS, HgS) and CdS/ZnSe superlattices. A distinction was reported between S-Zn and S-Cd bonds in the superlattices using fluorescence transitions involving metal d-state derived valence bands and S 2p core holes.…”
Section: Chemical State Analysis and Speciationmentioning
confidence: 99%
“…In addition to the observed chemical line shifts, the spectral shapes now vary for different compounds offering high sensitivity for the differentiation of sulfur compounds. Together with the suitable photon attenuation lengths in the soft x-ray range, this makes S L2,3 XES a very versatile technique for the investigation of fundamental and applied material systems like thin-film solar cells 7,8,[26][27][28][29] , CdS nanoparticles 30 , or CdS/ZnSe superlattices 31 . Already in early pioneering work, the S L2,3 XES spectra of sulfates were investigated and found to be very distinct from other sulfide compounds [32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Together with the suitable photon attenuation lengths in the soft X-ray range, this makes S L 2,3 XES a very versatile technique for the investigation of fundamental and applied material systems like thin-film solar cells, 7,8,26−29 CdS nanoparticles, 30 or CdS/ZnSe superlattices. 31 Already in early pioneering work, the S L 2,3 XES spectra of sulfates were investigated and found to be very distinct from other sulfide compounds. 32−35 In later studies, improved energy resolution allowed a better distinction between different sulfur species, but the spectra of different sulfates still are very similar, 7 as is the case for their K β spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft X-ray emission spectroscopy (SXES) is a well established tool for studying the electronic properties in solids and has already been used successfully for the characterization of thin film applications such as, for example, solar cells (Heske et al, 1999(Heske et al, , 2003Weinhardt et al, 2007;Rusu et al, 2009). It offers several important useful features: (i) it is element-specific; (ii) the peak position and spectral shape can offer information on the local chemical environment of the probed element owing to the involvement of valence band states and the high-energy resolution; (iii) as a photon-in-photon-out process with an information depth of between several nanometres and a few hundred nanometres it is more bulk-sensitive compared with surface-sensitive X-ray methods such as photoelectron or Auger-electron spectroscopy and is therefore a complementary method.…”
Section: Introductionmentioning
confidence: 99%